Legal Protection Against the Transfer of Fiducia Rights in the Takeover of Creditors - Suwarno, Ernawati; Suriaatmadja, Toto Tohir; Kurrohman, Taufik (Sinergi International Journal of Law, 2026)
Fiduciary security is a form of collateral over property or material security over movable objects, both tangible and intangible, which remain in the control of the fiduciary. This means that the pledged object is not physically handed over to the beneficiary, but the security right over it is recorded through a deed and registered at the fiduciary registration office. The construction of a fiduciary guarantee is the transfer of property rights in trust, over the debtor's property or movable goods to the creditor with physical control over the goods remaining with the debtor. Provided that if the debtor repays the debt in accordance with the stipulated time, the creditor is obliged to return the title to the property or goods to the debtor. In the repertoire of legal science, the transfer of property like this is called "Constitutum Possessorium." With the aim of knowing the legal protection of the transfer of fiduciary rights in law number 42 of 1999 concerning fiduciary guarantees and knowing the legal certainty in the takeover of creditors. This research method uses the foundation of the answer to the formulation of the problem is to use the main basis of the approach of legislation (Statue Approach) and conceptual approach (conceptual approach). The results of this study can be formulated that in the transfer of fiduciary rights in terms of the fiduciary law there is no mention of the fiduciary transfer process, while in the takeover of creditors it is mentioned in the limited liability company law that debts and shares in the form of assets all switch.